Flexible corrosion-resistant carbon nanotube electromagnetic shielding film and preparation method thereof

By growing amorphous pyrolytic carbon on the carbon nanotube film, the problem of carbon nanotube electromagnetic shielding materials not resistant to strong acid corrosion is solved, and efficient electromagnetic shielding performance and good corrosion resistance are achieved.

CN119789402AActive Publication Date: 2025-04-08NORTHWESTERN POLYTECHNICAL UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510044649.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-12
Publication Date
2025-04-08
Estimated Expiration
2045-01-12

AI Technical Summary

Technical Problem

Electromagnetic shielding materials based on carbon nanotubes are not resistant to strong acid corrosion, and there are relatively few existing studies in this regard.

Method used

Chemical vapor permeation method or chemical vapor deposition method is used to grow amorphous pyrolytic carbon on the surface and inside of the crystalline carbon nanotube film, thereby forming a carbon nanotube film composed of crystalline carbon nanotubes and amorphous pyrolytic carbon.

Benefits of technology

By introducing amorphous pyrolytic carbon, the corrosion resistance of the carbon nanotube film is enhanced, while maintaining the flexibility and high conductivity of the film, improving the electromagnetic shielding efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789402A_ABST
    Figure CN119789402A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible corrosion-resistant carbon nanotube electromagnetic shielding film and a preparation method thereof, and relates to the technical field of electromagnetic shielding. The carbon nanotube electromagnetic shielding thin film comprises a crystalline carbon nanotube thin film and amorphous pyrolytic carbon loaded on the surface and the interior of the crystalline carbon nanotube thin film; and carbon nanotubes in the crystalline carbon nanotube film are mutually overlapped to form a three-dimensional network structure. After the amorphous pyrolytic carbon is deposited on the surface of the original carbon nanotube film, corrosion can be prevented from expanding inwards, and therefore the overall corrosion resistance of the film is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electromagnetic shielding, and in particular to a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film and a preparation method thereof. Background Art

[0002] In recent years, with the development of portable electronic devices and wireless communication technology, it has brought convenience to people while also causing serious electromagnetic interference. Harmful electromagnetic interference not only causes temporary or permanent failure of electronic systems, but is also harmful to the surrounding environment and human health. Therefore, the development of efficient shielding materials has become an important means to reduce electromagnetic interference and solve electromagnetic problems, and is a key research area in current materials science.

[0003] In addition to high shielding performance, excellent shielding materials should also be ultra-light, ultra-thin, high-strength and flexible, especially for aircraft, spacecraft, drones, portable devices and wearable electronic products. Currently, most commercial electromagnetic shielding materials are metal materials with high electrical conductivity, but metal materials have the disadvantages of poor flexibility, corrosion resistance and high density. Carbon nanotubes (CNTs) have attracted widespread attention due to their unique properties, such as excellent electrical conductivity, tensile strength, high toughness, and low density. CNT-based electromagnetic shielding films and their composite materials have been widely used in the field of electromagnetic shielding. For example, CNT materials doped with highly conductive components can obtain electromagnetic shielding effectiveness higher than that of single-component materials, but because CNT itself cannot withstand the corrosion of certain strong proton acids, such as chlorosulfonic acid (CSA) and high concentrations of sulfuric acid and hydrochloric acid, the composite materials still show weak corrosion resistance. Therefore, in general, electromagnetic shielding materials based on carbon nanotubes still face the problem of being not resistant to strong acid corrosion, and there are relatively few studies in this area. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problem that electromagnetic shielding materials based on carbon nanotubes are still not resistant to strong acid corrosion. The present invention provides a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film and a preparation method thereof. The carbon nanotube film is composed of a crystalline carbon nanotube film and amorphous pyrolytic carbon. A layer of amorphous pyrolytic carbon grows uniformly on its surface, and the internal structure is that a single carbon nanotube is surrounded by amorphous pyrolytic carbon, and amorphous pyrolytic carbon also grows between adjacent carbon nanotubes. After the amorphous pyrolytic carbon is deposited on the surface of the original carbon nanotube film, it will prevent the corrosion from expanding inward, thereby enhancing the overall corrosion resistance of the film.

[0005] The first object of the present invention is to provide a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film, comprising a crystalline carbon nanotube film, and amorphous pyrolytic carbon loaded on the surface and inside of the crystalline carbon nanotube film;

[0006] The carbon nanotubes in the crystalline carbon nanotube film are overlapped with each other to form a three-dimensional network structure.

[0007] Preferably, the thickness of the crystalline carbon nanotube film is 6-8 μm.

[0008] Preferably, in the carbon nanotube electromagnetic shielding film, a layer of amorphous pyrolytic carbon grows on the surface of the crystalline carbon nanotube film, and the internal structure is that a single carbon nanotube is surrounded by amorphous pyrolytic carbon, and amorphous pyrolytic carbon also grows between adjacent carbon nanotubes.

[0009] Preferably, the carbon nanotube electromagnetic shielding film has a thickness of 10-15 μm.

[0010] The second object of the present invention is to provide a method for preparing a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film, comprising the following steps:

[0011] The crystalline carbon nanotube film is subjected to chemical vapor infiltration or chemical vapor deposition to grow amorphous pyrolytic carbon on the surface and inside thereof, thereby obtaining a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film.

[0012] Preferably, the treatment temperature of the chemical vapor infiltration method or the chemical vapor deposition method is 870-900° C., the treatment time is 36-48 hours, and the treatment pressure is 3-5 kPa.

[0013] Preferably, during the chemical vapor infiltration or chemical vapor deposition process, the carbon source used includes propylene and / or methane.

[0014] The third object of the present invention is to provide a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film for use in electromagnetic shielding.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention provides a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film and a preparation method thereof. The amorphous pyrolytic carbon itself contains carbon sp 3 Hybridization, which has good corrosion resistance, will prevent corrosion from spreading inward after being deposited on the surface of the original carbon nanotube film, thereby enhancing the corrosion resistance of the film as a whole. In the present invention, the amorphous pyrolytic carbon and the original carbon nanotubes are both carbonaceous materials. During the high-temperature CVI process, the pyrolytic carbon and the carbon nanotubes can form carbon sp 3Hybridization further enhances the corrosion resistance of the film, while improving the structural stability and density of the film. The pyrolytic carbon in the present invention also has the characteristics of lightness due to its carbonaceous material basis. After the introduction of pyrolytic carbon, the film still maintains the characteristics of lightness. The pyrolytic carbon in the present invention also has the characteristics of high electrical conductivity due to its carbonaceous material basis. After the introduction of pyrolytic carbon, the film still maintains high electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image (SEM) of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 of the present invention;

[0018] Figure 2 This is a transmission electron microscope image (TEM) of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 of the present invention;

[0019] Figure 3 This is a Raman spectra of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 of the present invention;

[0020] Figure 4 The stress-strain curve and bending diagram of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 of the present invention;

[0021] Figure 5 This is a conductivity diagram of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 of the present invention after corrosion resistance testing;

[0022] Figure 6 This is a graph showing the electromagnetic shielding effectiveness of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 of the present invention after corrosion resistance testing;

[0023] Figure 7 Actual picture of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film provided in Example 1. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0025] The purpose of the present invention is to solve the problem that electromagnetic shielding materials based on carbon nanotubes are not resistant to strong acid corrosion, and to provide a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film and a preparation method thereof.

[0026] In order to achieve the above-mentioned object, the first aspect of the present invention provides a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film, comprising a crystalline carbon nanotube film, and amorphous pyrolytic carbon loaded on the surface and inside of the crystalline carbon nanotube film;

[0027] The carbon nanotubes in the crystalline carbon nanotube film are overlapped with each other to form a three-dimensional network structure.

[0028] The carbon nanotube film provided by the present invention has good electromagnetic shielding performance, good flexibility and excellent corrosion resistance.

[0029] The thickness of the crystalline carbon nanotube film is 6-8 μm.

[0030] In the carbon nanotube electromagnetic shielding film, a layer of amorphous pyrolytic carbon grows on the surface of the crystalline carbon nanotube film, and the internal structure is that a single carbon nanotube is surrounded by amorphous pyrolytic carbon, and amorphous pyrolytic carbon also grows between adjacent carbon nanotubes.

[0031] The thickness of the carbon nanotube electromagnetic shielding film is 10-15 μm.

[0032] A second aspect of the present invention provides a method for preparing a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film, comprising the following steps:

[0033] The crystalline carbon nanotube film is subjected to chemical vapor infiltration or chemical vapor deposition to grow amorphous pyrolytic carbon on the surface and inside thereof, thereby obtaining a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film.

[0034] The treatment temperature of the chemical vapor infiltration method or the chemical vapor deposition method is 870-900° C., the treatment time is 36-48 hours, and the treatment pressure is 3-5 kPa.

[0035] In the chemical vapor infiltration or chemical vapor deposition process, the carbon source used includes propylene and / or methane.

[0036] The present invention uniformly grows pyrolytic carbon on the surface and inside of a crystalline carbon nanotube film, thereby obtaining a carbon nanotube film composed of crystalline carbon nanotubes and amorphous pyrolytic carbon. A layer of amorphous pyrolytic carbon is uniformly grown on the surface, and the internal structure is that a single carbon nanotube is surrounded by amorphous pyrolytic carbon, and amorphous pyrolytic carbon is also grown between adjacent carbon nanotubes. The thickness of the original carbon nanotube film is 6 to 8 μm, and the thickness of the film after the introduction of amorphous pyrolytic carbon is 10 to 15 μm. The carbon nanotubes in the carbon nanotube film overlap each other to form a three-dimensional network structure, thereby enhancing the corrosion resistance of the entire film.

[0037] Exemplarily, a method for preparing a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film comprises the following steps:

[0038] treating the crystalline carbon nanotube film by chemical vapor infiltration;

[0039] Amorphous pyrolytic carbon grows on the surface and inside of the treated crystalline carbon nanotube film, thereby obtaining a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film.

[0040] The chemical vapor infiltration treatment temperature is 870-900°C, the treatment time is 36-48h, the treatment pressure is 5kPa, and the carbon source used for treatment includes propylene (C3H6), methane (CH4) or a combination of the two gases, preferably propylene.

[0041] Exemplarily, a method for preparing a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film comprises the following steps:

[0042] Processing a crystalline carbon nanotube film by chemical vapor deposition;

[0043] Amorphous pyrolytic carbon grows on the surface and inside of the treated crystalline carbon nanotube film, thereby obtaining a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film.

[0044] The chemical vapor deposition method has a processing temperature of 870-900°C, a processing time of 36-48 hours, a processing pressure of 5 kPa, and a carbon source for processing includes propylene (C3H6), methane (CH4) or a combination of the two gases, preferably propylene.

[0045] A third aspect of the present invention provides an application of a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film in electromagnetic shielding.

[0046] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0047] Example 1

[0048] A method for preparing a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film comprises the following steps:

[0049] A 6 μm thick original carbon nanotube film is placed on a heating table in a heating furnace, and carbon source propylene is introduced. The temperature is set to 870°C, the pressure is set to 5 kPa, and the temperature is kept warm for 36 hours. Amorphous pyrolytic carbon grows evenly on the surface and inside of the original carbon nanotube film to obtain a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film PyC-CNT.

[0050] Example 2

[0051] A method for preparing a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film comprises the following steps:

[0052] A 6 μm thick original carbon nanotube film is placed on a heating table in a heating furnace, and carbon source propylene is introduced. The temperature is set to 870°C, the pressure is set to 5 kPa, and the temperature is kept warm for 48 hours. Amorphous pyrolytic carbon grows evenly on the surface and inside of the original carbon nanotube film to obtain a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film PyC-CNT-1.

[0053] Example 3

[0054] A pristine carbon nanotube film with a thickness of 8 μm was placed on a heating table in a heating furnace, and carbon source methane was introduced. The temperature was set to 870°C, the pressure was set to 5 kPa, and the temperature was kept at this temperature for 36 hours. Amorphous pyrolytic carbon grew evenly on the surface and inside of the pristine carbon nanotube film to obtain the sample PyC-CNT-2.

[0055] In order to illustrate the relevant properties of the flexible corrosion-resistant carbon nanotube electromagnetic shielding film provided by the present invention, the original carbon nanotube film in Example 1 and the prepared flexible corrosion-resistant carbon nanotube electromagnetic shielding film were characterized in terms of microscopic morphology and performance:

[0056] Figure 1 The SEM images of the original carbon nanotube film (CNT) and the flexible corrosion-resistant carbon nanotube electromagnetic shielding film (PyC-CNT) prepared in Example 1 are shown respectively, and the magnification is 50,000 times. Figure 1 As can be seen from the left picture (CNT), the single carbon nanotubes in the original carbon nanotube film overlap and entangle with each other to form a three-dimensional network structure, and there are granular impurities in the network structure. The impurities may be residual metal catalysts. The presence of impurities will affect the conduction efficiency of electrons in the carbon nanotube network, thereby affecting the conductivity of the film, and ultimately leading to a decrease in the electromagnetic shielding effectiveness of the film. After chemical vapor infiltration treatment, Figure 1 As can be seen in the right picture (PyC-CNT), a dense layer of pyrolytic carbon is deposited on the surface of the original carbon nanotube film. Pyrolytic carbon and carbon nanotubes are both carbon materials, so when pyrolytic carbon is introduced, a carbon sp 3 Hybridization, while the bonding mode of pyrolytic carbon itself includes sp 3 Hybridization, compared with the sp 2 Hybridization, sp 3 Hybridization will enhance the bonding force between materials and make the materials denser, so the introduction of pyrolytic carbon will improve the overall performance of carbon nanotube films, especially the corrosion resistance of the films.

[0057] Figure 2 The TEM image of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film (PyC-CNT) prepared in Example 1 is shown. Figure 2In the figure, a single crystalline carbon nanotube with concentric transmission stripes can be seen, and amorphous pyrolytic carbon is distributed around it. This proves that the chemical vapor infiltration method has successfully grown amorphous pyrolytic carbon inside the film and wrapped the crystalline carbon nanotubes. The carbon nanotubes are also filled with pyrolytic carbon, which enhances the structural stability and corrosion resistance of the film.

[0058] Figure 3 The Raman spectra of the original carbon nanotube film (CNT) and the flexible corrosion-resistant carbon nanotube electromagnetic shielding film (PyC-CNT) prepared in Example 1 are shown. It can be seen that both samples show obvious carbon characteristic peaks, including 1340 cm -1 D belt and 1590cm -1 After the introduction of pyrolytic carbon, the ratio of D band to G band (I D / I G ) has a significant increase, from 0.284 to 0.903, which means that the decrease in the degree of graphitization of the sample corresponds to the introduction of amorphous pyrolytic carbon.

[0059] Figure 4 The stress-strain curves and bending diagrams of the original carbon nanotube film and the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 are shown. It can be seen that after the introduction of pyrolytic carbon, the maximum tensile stress of the sample is increased from 20Mpa to 110Mpa. This is due to the sp3 hybridization of carbon introduced when the pyrolytic carbon is introduced, which enhances the bonding force between the materials and greatly improves the mechanical properties of the film. At the same time, Figure 7 The flexible, corrosion-resistant carbon nanotube electromagnetic shielding film provided in Example 1 can be shown in the actual pictures of bending and rolling to show that the film has excellent flexibility and can adapt to various complex-shaped surfaces, thereby providing electromagnetic shielding function.

[0060] Figure 5 The conductivity diagrams after the corrosion test of the original carbon nanotube film and the flexible corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 are shown. The corrosion test environment includes chlorosulfonic acid solution (CSA, 99wt%), sulfuric acid solution (95%~98%wt%), hydrochloric acid solution (36%~38%wt%), and the corrosion time is 45 days. The specific operation is: completely immerse the film in a glass bottle containing the above solution for 45 days. It can be seen that the conductivity of the flexible corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 is improved to a certain extent compared with the original carbon nanotube film. This is due to the sp of carbon introduced by pyrolytic carbon. 3Hybridization makes the film structure more compact and enhances the efficiency of electron transfer. The conductivity of the film is further improved after the corrosion test. This is because the particle impurities in the original carbon nanotube film are removed after immersion, which enhances the efficiency of electron transfer. And after being treated with chlorosulfonic acid solution, the conductivity of the film is improved the most. This is because chlorosulfonic acid has high polarity. After the carbon nanotube film is treated with chlorosulfonic acid, it will further induce charge separation on a single carbon nanotube, produce positive charge areas and negative charge areas, and increase the positive and negative charge sites on the tube. Under the action of Coulomb charge and van der Waals force, the connection sites between carbon nanotubes increase, and the connection is tighter, achieving a densification effect. Because the connection sites between carbon nanotubes increase, the transmission speed of electrons in them is faster, and the conductivity is greatly improved.

[0061] Figure 6 The electromagnetic shielding effectiveness of the carbon nanotube film prepared in Example 1 in the X-band is demonstrated. It can be seen that the flexible and corrosion-resistant carbon nanotube electromagnetic shielding film prepared in Example 1 exhibits good electromagnetic shielding performance and corrosion resistance, and the shielding effectiveness can reach up to 48.8dB. And as theoretically analyzed, the deposition of pyrolytic carbon enhances the corrosion resistance of the carbon nanotube film, and the electromagnetic shielding performance of the film is further improved after being corroded by an acid solution for 45 days. In particular, the prepared flexible and corrosion-resistant carbon nanotube electromagnetic shielding film withstands long-term corrosion by a chlorosulfonic acid solution, and the electromagnetic shielding effectiveness of the film after corrosion is improved to a maximum of 57dB.

[0062] In summary, the present invention provides a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film and a preparation method thereof, specifically: treating a crystalline carbon nanotube film by chemical vapor infiltration, and growing amorphous pyrolytic carbon on the surface and inside of the treated carbon nanotube film, thereby obtaining a flexible, corrosion-resistant carbon nanotube electromagnetic shielding film. The flexible, corrosion-resistant carbon nanotube electromagnetic shielding film prepared by the present invention has good flexibility, exhibits a shielding effectiveness of up to 48.8dB in the X-band, can withstand long-term corrosion by high-concentration acid solutions, and the shielding effectiveness is further improved after being corroded by acid solutions, so it is expected to be used in the field of electromagnetic shielding.

[0063] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A flexible, corrosion-resistant carbon nanotube electromagnetic shielding film, characterized in that: It includes a crystalline carbon nanotube film and amorphous pyrolytic carbon loaded on the surface and inside of the crystalline carbon nanotube film; The carbon nanotubes in the crystalline carbon nanotube film are overlapped with each other to form a three-dimensional network structure.

2. The flexible, corrosion-resistant carbon nanotube electromagnetic shielding film according to claim 1, characterized in that: The thickness of the crystalline carbon nanotube film is 6-8 μm.

3. The flexible, corrosion-resistant carbon nanotube electromagnetic shielding film according to claim 1, characterized in that: In the carbon nanotube electromagnetic shielding film, a layer of amorphous pyrolytic carbon grows on the surface of the crystalline carbon nanotube film, and the internal structure is that a single carbon nanotube is surrounded by amorphous pyrolytic carbon, and amorphous pyrolytic carbon also grows between adjacent carbon nanotubes.

4. The flexible, corrosion-resistant carbon nanotube electromagnetic shielding film according to claim 1, characterized in that: The thickness of the carbon nanotube electromagnetic shielding film is 10-15 μm.

5. A method for preparing the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film according to any one of claims 1 to 4, characterized in that: The following steps are involved: The crystalline carbon nanotube film is subjected to chemical vapor infiltration or chemical vapor deposition to grow amorphous pyrolytic carbon on the surface and inside thereof, thereby obtaining a flexible and corrosion-resistant carbon nanotube electromagnetic shielding film.

6. The method for preparing the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film according to claim 5, characterized in that: The treatment temperature of the chemical vapor infiltration method or the chemical vapor deposition method is 870-900° C., the treatment time is 36-48 hours, and the treatment pressure is 3-5 kPa.

7. The method for preparing the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film according to claim 6, characterized in that: In the chemical vapor infiltration or chemical vapor deposition process, the carbon source used includes propylene and / or methane.

8. Use of the flexible, corrosion-resistant carbon nanotube electromagnetic shielding film according to any one of claims 1 to 4 in electromagnetic shielding.

Citation Information

Patent Citations

  • Preparation method for carbon nano tube enhanced pyrolytic carbon material

    CN107010978A

  • Method for preparing carbon nanotube electromagnetic shielding film

    CN109729707A

  • Carbon nanotube / graphene / polymer electromagnetic shielding material, preparation method and application thereof

    CN109762339A

  • Carbon nanotube foam material with electromagnetic shielding performance, and preparation method and application thereof

    CN112210766A

  • Carbon / carbon composite film with high resilience in extreme environment as well as preparation method and application of carbon / carbon composite film

    CN114516201A